PENGARUH DISTRESS PSIKOLOGIS TERHADAP PERUBAHAN PERILAKU MENYIMPANG PADA REMAJA DI DUREN MEKAR - Hanum, Mutiara; Ati Kusmawati (JOURNAL SAINS STUDENT RESEARCH, 2025)
Adolescence is a transitional phase in individual development, from childhood to adulthood. During this period, adolescents experience significant physical, emotional, and social events. The presence of psychological pressure, such as anxiety, and stress can be a factor in adolescent well-being and development. Stress can be triggered by something and will disappear after life events change. In real terms, it can affect emotional abilities that are unstable and physical conditions can be disturbed. The things they feel from sexual harassment (verbal) can also trigger psychological stress. Stress can trigger adolescents to commit other deviant acts. This study aims to determine changes in deviant behavior in adolescents in Duren Mekar Village who experience low or high levels of psychological distress. The research method used is a quantitative method with a data collection technique in the form of a questionnaire. The results of the study showed that between these variables at a relatively low level of 15.5%.